An artificial immune system (AIS) application to reactive power dispatch for loss minimization in distribution system - Ahmad Faiz, Noor Azam (Universiti Malaysia Perlis (UniMAP), 2009)
This project presents voltage control methods to improve the voltage level of a power system whilst minimizing losses. Newton Raphson method is used to calculate losses to control the operation of reactive power dispatch and tap changing transformer to minimize losses. Uncontrolled reactive power flow in an industrial distribution system can give rise to excessive active and reactive power losses and voltage drops on steadystate load flow. In an interconnected distribution system with cogeneration, voltage drops under contingency conditions, i.e. on loss of a generator or tie line, can disrupt the continuous processes. The active power rating of the distribution system components can be seriously degraded. The test system that is used for the project is a six bus system and the program is done using MATLAB software.